2002
DOI: 10.1200/jco.2002.08.149
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemotherapy-Radiotherapy Compared With Radiotherapy Alone in Locoregionally Advanced Nasopharyngeal Carcinoma: Progression-Free Survival Analysis of a Phase III Randomized Trial

Abstract: Concurrent CRT is well tolerated in patients with advanced NPC in endemic areas. Although PFS was not significantly different between the concurrent CRT arm and the RT-alone arm in the overall comparison, PFS was significantly prolonged in patients with advanced tumor and node stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
292
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(307 citation statements)
references
References 21 publications
(14 reference statements)
10
292
2
3
Order By: Relevance
“…To the best of our knowledge, there have been nine phase III randomised trials to investigate the role of combined chemoradiotherapy in NPC so far (Rossi et al, 1988;Chan et al, 1995Chan et al, , 2002Cvitkovic and INCSG, 1996;Al-Sarraf et al, 1998;Chua et al, 1998;Ma et al, 2001;Chi et al, 2002;Hareyama et al, 2002). Table 5 summarises the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there have been nine phase III randomised trials to investigate the role of combined chemoradiotherapy in NPC so far (Rossi et al, 1988;Chan et al, 1995Chan et al, , 2002Cvitkovic and INCSG, 1996;Al-Sarraf et al, 1998;Chua et al, 1998;Ma et al, 2001;Chi et al, 2002;Hareyama et al, 2002). Table 5 summarises the results.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the only randomised trial of positive results in survival analysis, its wide application to non-American NPC patients should be considered with caution. First, about 30% patients of the Intergroup study have WHO type I histology (keratinising squamous cell carcinoma), but European (Cvitkovic et al, 1996), Japanese (Hareyama et al, 2002), or Chinese (Chan et al, 1995(Chan et al, , 2002Chua et al, 1998;Ma et al, 2001;Chi et al, 2002) series usually contain less than 5% WHO type I patients. Second, the survival data of radiotherapy alone are unexplainedly low -24% 3-year progression-free survival rate and 47% 3-year overall survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39] One negative adjuvant chemotherapy trial used a noncisplatin combination and was carried on before the introduction of cisplatin-5FU in this disease. Of four induction chemotherapy trials, two used combinations without cisplatin-5FU, and the other two used cisplatin-5FU combinations.…”
Section: Nasopharyngeal Cancermentioning
confidence: 99%
“…However in patients with more advanced disease stages (UICC stage III and IV), recurrence is common and, consequently, 5-yr survival rates are only 45-60%. Recent studies have demonstrated an improvement of progression-free survival with concurrent cisplatin and RT compared with RT alone, and the improvement was statistically significant in patients with advanced disease (12). Unfortunately concurrent cisplatin and RT resulted in considerable toxicity.…”
Section: Discussionmentioning
confidence: 99%